Answer:
ajkskakakna
Step-by-step explanation:
babcdsjj no te preocupes por qué no me deja
Answer: 3a
2
(5a+2b)−5b
2
(5a+2b)
2 Factor out the common term 5a+2b5a+2b.
(5a+2b)(3{a}^{2}-5{b}^{2})(5a+2b)(3a
2
−5b
2
)
Step-by-step explanation:
10,000 people make less than $15,000. To find the answer you just divide 40,000 by 4.
Since both terms are perfect cubes, factor using the difference of cubes formula,
a
3
−
b
3
=
(
a
−
b
)
(
a
2
+
a
b
+
b
2
)
a
3
-
b
3
=
(
a
-
b
)
(
a
2
+
a
b
+
b
2
)
where
a
=
x
2
a
=
x
2
and
b
=
y
b
=
y
.
(
x
2
−
y
)
(
(
x
2
)
2
+
x
2
y
+
y
2
)
(
x
2
-
y
)
(
(
x
2
)
2
+
x
2
y
+
y
2
)
Multiply the exponents in
(
x
2
)
2
(
x
2
)
2
.